Find ∫ sec x /(1 + cosec x) dx
This is a question of CBSE Sample Paper - Class 12 - 2017/18.
You can download the question paper here https://www.teachoo.com/cbse/sample-papers/
CBSE Class 12 Sample Paper for 2018 Boards
Question 1 Important
Question 2 Important
Question 3
Question 4
Question 5
Question 6 Important
Question 7 Important
Question 8
Question 9 Important
Question 10
Question 11 Important
Question 12
Question 13 Important
Question 14 Important
Question 15
Question 16 Important
Question 17
Question 18 Important You are here
Question 19
Question 20 Important
Question 21 Important
Question 22
Question 23
Question 24 Important
Question 25
Question 26 Important
Question 27
Question 28 Important
Question 29
CBSE Class 12 Sample Paper for 2018 Boards
Last updated at April 16, 2024 by Teachoo
This is a question of CBSE Sample Paper - Class 12 - 2017/18.
You can download the question paper here https://www.teachoo.com/cbse/sample-papers/
Question 18 Find β«1βsecβ‘π₯/(1 + πππ ππ π₯) dx β«1β(π ππ π₯)/(1 + πππ ππ π₯) ππ₯ = β«1β(1/πππ β‘π₯ )/(1 + 1/π ππβ‘π₯ ) ππ₯ = β«1β(1/πππ β‘π₯ )/((π ππβ‘π₯ + 1)/π ππβ‘π₯ ) ππ₯ = β«1βγ1/πππ β‘π₯ Γ sinβ‘π₯/(π ππβ‘π₯ + 1)γ ππ₯ = β«1β(π ππ π₯)/(πππ π₯(1 + π ππ π₯)) ππ₯ Multiplying and dividing by cos x = β«1β(π ππ π₯)/(πππ π₯(1 + π ππ π₯)) Γcosβ‘π₯/cosβ‘π₯ ππ₯ = β«1β(π ππ π₯ cosβ‘π₯)/(cos^2β‘π₯ (1 + π ππ π₯)) ππ₯ Using cos2 x = 1 β sin2 x = β«1β(π ππ π₯ cosβ‘π₯)/((1 β sin^2β‘π₯ )(1 + sinβ‘γπ₯)γ ) ππ₯ = β«1β(π ππ π₯ cosβ‘π₯)/( (1 β sinβ‘γπ₯)γ (1 + sinβ‘γπ₯)γ (1 + sinβ‘γπ₯)γ ) ππ₯ = β«1β(π ππ π₯ cosβ‘π₯)/((1 + γsinβ‘γπ₯)γγ^2 (1 β sinβ‘γπ₯)γ ) ππ₯ Let sin x = t β΄ cos x dx = dt Putting values in equation = β«1β(π‘ )/((1 + π‘)^2 (1 β π‘)) dt We solve this by partial fractions We can write the integrand as π‘/((1 + π‘)^2 (1 β π‘)) = π΄/(1 + π‘) + π΅/(1 + π‘)^2 + πΆ/(1 β π‘) π‘/((1 + π‘)^2 (1 β π‘)) = (π΄(1 + π‘)(1 β π‘) + π΅(1 β π‘) + πΆ(1 + π‘)^2)/((1 + π‘)^2 (1 β π‘)) By cancelling denominator π‘ = π΄(1 + π‘)(1 β π‘) + π΅(1 β π‘) + πΆ(1 + π‘)^2 Putting t = β1 in (1) β1 = π΄(1+(β1))(1 β(β1)) + π΅(1 β(β1)) + πΆ(1 +(β1))^2 β1 = AΓ0+BΓ2+C(0)^2 β1 = 2B 2B = β1 B = (β1)/2 Putting t = 1 in (1) 1 = π΄(1+1)(1 β1) + π΅(1 β1) + πΆ(1 +1)^2 1 = AΓ0+BΓ0+C(2)^2 1 = 4C 4C = 1 C = 1/4 Putting t = 0 in (1) 0 = π΄(1+0)(1 β0) + π΅(1 β0) + πΆ(1 +0)^2 0 = π΄(1)(1) + π΅(1) + πΆ(1)^2 0 = A+B+C 0 = A + ((β1)/2) + 1/4 1/2β1/4 = A 1/4 = A A = 1/4 Hence we can write β«1β(π‘ )/((1 + π‘)^2 (1 β π‘)) dt = β«1β(1/4)/((1 + π‘) ) dt + β«1β((β1)/2)/(1 + π‘)^2 dt + β«1β(1/4)/( (1 β π‘)) dt